2013
DOI: 10.9790/487x-0844052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Management Control to Organizational Culture, Compensation, Work Behavior and Employees Performance. (Studies in the Village Unit Cooperatives (KUD) in Southeast Sulawesi)

Abstract: Data collection is done by distributing questionnaires followed by in-depth interviews (in-depth). This study used descriptive analysis to determine the characteristics of the respondent and respondent description of indicators each study variable. While to examine the pattern of relationships between the study variables used inferential analysis tool that analyzes point to the approach of SPSS version 20.The results of this study indicate that adequate management controls to improve employee performance when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…And that what motivates one person might not motivate another and therefore, for the best results any manager should understand and as far as feasible, get to know something about each of his/her subordinates (Abbah, 2014). Nurwati (2013) refers to control function (controlling) as a role to detect potential weaknesses that occur as a feedback to the management of an activity, starting from the planning stage to the implementation stage. Controlling of resources function includes the creation of standards or criteria, comparing results with standard monitoring, the implementation of an improvement over the deviation or aberration, modification and adjustment of the changing conditions, as well as communicating the revisions and adjustments of process management so that irregularities or flaws are not repeated again (Nurwati, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…And that what motivates one person might not motivate another and therefore, for the best results any manager should understand and as far as feasible, get to know something about each of his/her subordinates (Abbah, 2014). Nurwati (2013) refers to control function (controlling) as a role to detect potential weaknesses that occur as a feedback to the management of an activity, starting from the planning stage to the implementation stage. Controlling of resources function includes the creation of standards or criteria, comparing results with standard monitoring, the implementation of an improvement over the deviation or aberration, modification and adjustment of the changing conditions, as well as communicating the revisions and adjustments of process management so that irregularities or flaws are not repeated again (Nurwati, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Nurwati (2013) refers to control function (controlling) as a role to detect potential weaknesses that occur as a feedback to the management of an activity, starting from the planning stage to the implementation stage. Controlling of resources function includes the creation of standards or criteria, comparing results with standard monitoring, the implementation of an improvement over the deviation or aberration, modification and adjustment of the changing conditions, as well as communicating the revisions and adjustments of process management so that irregularities or flaws are not repeated again (Nurwati, 2013). Olusanya, Awotunggase & Ohadebere (2012) indicated that planning involves selecting from among alternative future course of action for the organization as a whole in every department or section.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Syauta et al (2012) who conducted research in Jayapura showed that organizational culture has no effect on performance. Furthermore Nurwati (2013) conducted research in Southeast Sulawesi, it is revealed that organizational culture has an influence one mployee performance.…”
Section: Relationship Between Organizational Culture and Performancementioning
confidence: 99%
“…Holt (1993), Hameed et al (2015), and Darmawan (2011). Robbins (1996), Gibson (1996) and Marwan et al (2009) as cited by Nurwati (2013), concluded that there is a positive influence between compensation and employee performance. It is also supported by the results of the study by Collins et al (2005); Teclemichael and Soeters (2006), which states the compensation a positive influence on the performance of employees.…”
Section: Competensation Effect On Performancementioning
confidence: 99%
“…Based on the above notions then, it can be said that the compensation is all forms of fringe benefits provided by the organization to a person or group of people for what they have done that is worth the amount of education and training and performance. Robbins (1996), Gibson (1996), and Marwan et al (2009) as cited by Nurwati (2013), concluded that there is a positive influence between compensation and employee performance. It is also supported by the results of the study by Collins et al (2005); Teclemichael and Soeters (2006), which states the compensation a positive influence on the performance of employees.…”
Section: Introductionmentioning
confidence: 99%